Determinants of spatial patterns of canopy tree species in a tropical evergreen forest in Gabon. (25th July 2019) - Engone Obiang, Nestor Laurier; Kenfack, David; Picard, Nicolas; Lutz, James A.; Bissiengou, Pulchérie; Memiaghe, Hervé R.; Alonso, Alfonso
Abstract: Questions: We examined the spatial patterns of dominant canopy species in a tropical forest to investigate: (a) what is the niche occupancy of canopy species with respect to topographic gradients; (b) what are the dominant ecological processes that explain their distribution; (c) what are the interactions among the most prevalent canopy species; and (d) what are the interactions between canopy species adults and juveniles trees? Location: Rabi permanent CTFS‐ForestGEO plot, Gabon. Methods: We selected the four most abundant canopy species and one timber species. We used Berman's test to determine the effect of three topographic variables on the distribution of each species and univariate analysis to model the spatial pattern of each species using either an inhomogeneous Poisson process or an inhomogeneous Cox process. We also used a bivariate form of the pair correlation function (PCF) to determine the spatial interaction between species and the correlation among conspecific adult and juvenile trees. Results: Four of the five species had aggregated spatial patterns while Lophira alata showed spatial randomness. Most of the variance in the local tree density was explained by within‐population dispersal processes rather than environmental factors. Bivariate PCF tests showed significant segregation between species associations. Two species exhibited aggregation at small distances between young and adult trees, while others showed either complete spatial randomness at small inter‐tree distances or segregation at large distances. Conclusions: This study showed that the spatial pattern in the majority of canopy species was aggregation. Seed dispersal limitation mainly explained the observed aggregation pattern. Habitat filtering, as evidenced by the influence of topographic variables on niche occupancy, marginally, yet significantly, explained this pattern. The different spatial patterns of the principal species permit their coexistence. Spatial segregation among adult and juvenile trees reveals a strong pattern of either species‐specific seed predation or pathogens. Abstract : Univariate spatial pattern of Lophira alata in the 25‐ha plot at Rabi Gabon. Solid black lines represent the observed pattern of inter‐tree distances; dashed red lines represent the predicted homogeneous Poisson process. Gray areas show the 95% confidence limits around the predicted pair correlation function (PCF) estimated from 100 random simulations of the point process.